2018
DOI: 10.1111/vsu.13117
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of peer teaching and deliberate practice to teach veterinary surgery

Abstract: Objective: To assess the impact of peer teaching and deliberate practice on surgical skills acquisition and retention in first-and second-year veterinary students. Study design: Randomized, prospective, comparative study. Sample population: Eighteen first-year and 25 second-year students from 1 college of veterinary medicine who had previously demonstrated proficiency in basic surgical skills. Methods: Forty-three participants were divided into 3 groups: the test group (group A, n = 15), who participated in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…9,15 Time to completion is often used as a proxy of skill proficiency, although it is not a consistent finding among novice learners. 23 Indeed, in this study, time to perform the procedure decreased 3-4 weeks after training, but there was no concurrent improvement in the quality of students' performance as assessed by the checklist or GRS.…”
Section: Skill Learning and Retentionmentioning
confidence: 50%
“…9,15 Time to completion is often used as a proxy of skill proficiency, although it is not a consistent finding among novice learners. 23 Indeed, in this study, time to perform the procedure decreased 3-4 weeks after training, but there was no concurrent improvement in the quality of students' performance as assessed by the checklist or GRS.…”
Section: Skill Learning and Retentionmentioning
confidence: 50%
“…Other studies on surgical learning note that surgical skills improve with practice; however, that improvement is usually based on duration of each attempt rather than the mechanical quality of the product ( Compton et al, 2019 ; Asadayoobi, Jaber & Taghipour, 2021 ; Gilmer et al, 2015 ). Improvement in hand tie scores was noticed over three practice periods when students practiced tying two-handed ties for 15 min intervals and then were filmed making three attempts at hand ties ( Thomas, Hayes & Demetriou, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Compton et 2019 study showed that students participating in a peer-assisted learning program had better surgical skills than both students participating in unsupervised deliberate practice and students who did not have a practice program. 56…”
Section: Peer-assisted Learningmentioning
confidence: 99%
“…In 2001 Hauptman et al described the successful use of fourth year veterinary students as tutors in third year students' live surgeries. Compton et al’s 2019 study showed that students participating in a peer‐assisted learning program had better surgical skills than both students participating in unsupervised deliberate practice and students who did not have a practice program 56 …”
Section: How Can Surgical Skills Learning Be Optimized?mentioning
confidence: 99%